2014
DOI: 10.14202/vetworld.2014.78-82
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inclusion of Azolla pinnata on the haematological and carcass characteristics of crossbred large white yorkshire pigs

Abstract: Aim: To study the haematological and carcass parameters of pigs fed with Azolla based rations. Materials and Methods:An experiment was done for 120 days using 18 crossbred Large White Yorkshire pigs fed with diets containing Azolla as protein replacement at 0, 10 and 20 percent, respectively. The mean haematological parameters of the three experimental groups were studied before start of an experiment, and during the grower phase and finisher phase. Two pigs from each group were slaughtered after 120 days of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 2 publications
3
7
1
Order By: Relevance
“…Overall average feed intake in terms of per cent body of crossbred growing pigs were 3.39±0.12, 3.37±0.16, and 3.46±0.19 per cent, respectively for the G1, G2, and G3 groups and no significant difference were observed among the experimental groups. The result obtained in the present study is in accordance with the reports of Cherryl et al, (2013). It is supported by the findings of Shamna et al, (2013), who have reported that growth and feed conversion efficiency in quails on Azolla pinnata at 5% displacement level of the basal ration was as good as the basal diet, besides it was more economical due to less expenditure on feed.…”
Section: Resultssupporting
confidence: 93%
“…Overall average feed intake in terms of per cent body of crossbred growing pigs were 3.39±0.12, 3.37±0.16, and 3.46±0.19 per cent, respectively for the G1, G2, and G3 groups and no significant difference were observed among the experimental groups. The result obtained in the present study is in accordance with the reports of Cherryl et al, (2013). It is supported by the findings of Shamna et al, (2013), who have reported that growth and feed conversion efficiency in quails on Azolla pinnata at 5% displacement level of the basal ration was as good as the basal diet, besides it was more economical due to less expenditure on feed.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, it was observed that there was no significant difference (p>0.05) between the means of PCV, Hb, RBC, W BC in all the three treatments at three stages of experiment. Similar observations were reported by Anitha et al (2016) in rabbits and Cherryl et al (2014) in pigs. Kumar et al (2016) in Barbari bucks observed that when 100 g of fresh azolla was fed per day under intensive system showed no significant difference between the means of Hb, RBC and W BC.…”
Section: Haematological Studiessupporting
confidence: 92%
“…The finding indicates no significant variations between the initial and final haematological values. This implies that the blood values are more or less similar to the reference values, implying that using Azolla in pig diets does not affect white Yorkshire pigs [22]. Similarly, the haematological profile of the Chabro chicken was unaffected by any treatment [18].…”
Section: Biological Effectsmentioning
confidence: 80%
“…Aside from that, turkeys [20] and broiler ducks [21] were analysed. Sows [14], white Yorkshire pigs [22], and buffaloes [6] were the only livestock that was tested. Broiler chickens are the most well-known poultry that several experts have extensively researched.…”
Section: Background Of Studies Reviewedmentioning
confidence: 99%
See 1 more Smart Citation